2023
DOI: 10.1136/jnis-2022-019741
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy decision making and prognostication: Stroke treatment Assessments prior to Thrombectomy In Neurointervention (SATIN) study

Abstract: BackgroundMechanical thrombectomy (MT) is the standard-of-care treatment for stroke patients with emergent large vessel occlusions. Despite this, little is known about physician decision making regarding MT and prognostic accuracy.MethodsA prospective multicenter cohort study of patients undergoing MT was performed at 11 comprehensive stroke centers. The attending neurointerventionalist completed a preprocedure survey prior to arterial access and identified key decision factors and the most likely radiographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…We recognize the limitations of any clinical prediction rule, as previously described, 5,6 and do not advocate making a definitive prognosis based on any single scale. However, incorporating an objective measure into an individual patient scenario may be better than using clinical subjectivity alone, given the previously reported poor prognostications of stroke physicians in case‐based scenarios versus a validated risk score 28,29 and prior to thrombectomy 30 …”
Section: Discussionmentioning
confidence: 99%
“…We recognize the limitations of any clinical prediction rule, as previously described, 5,6 and do not advocate making a definitive prognosis based on any single scale. However, incorporating an objective measure into an individual patient scenario may be better than using clinical subjectivity alone, given the previously reported poor prognostications of stroke physicians in case‐based scenarios versus a validated risk score 28,29 and prior to thrombectomy 30 …”
Section: Discussionmentioning
confidence: 99%
“…This consideration is in agreement with the claim made by DAWN author Dr. Raul Nogueira, who suggests that the selection criteria used are more useful as predictors of outcome rather than hardline decisionmaking parameters, and that to adhere to the boundaries provided by the DAWN or DEFUSE-3 protocols would be to deny an effective treatment to many other deserving stroke patients [6]. Also, a recent study of neuro-interventionists' prognostic ability to predict post-mechanical thrombectomy outcomes revealed low accuracy given pre-procedure information [7]. Of note, there is currently no posited target for a hit or miss rate associated with the radiographic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Large core stroke thrombectomy: paradigm shift or futile exercise? Michael Chen , 1 Thabele M Leslie-Mazwi, 2 Joshua A Hirsch , 3 Felipe C Albuquerque 4 Predicting treatment effect is a popular topic among recent Journal of Neurointerventional Surgery stroke thrombectomy publications. [1][2][3] The primary outcome measure is often functional independence, that is, a modified Rankin Scale (mRS) score of 0-2, which may lead practitioners to ruminate on the probability of this outcome during stroke triage, instead of treating patients with thrombectomy.…”
mentioning
confidence: 99%
“…In fact, the recent Stroke treatment Assessments prior to Thrombectomy In Neurointervention (SATIN) study demonstrated that neurointerventionalists were only accurate in predicting outcomes 44% of the time, including being overly pessimistic at times when outcomes were better than expected. 4 It is no wonder that the majority of malpractice lawsuits related to acute stroke treatment allege failure to treat. 5 From the patient's perspective, the most terrifying, costly and overlooked outcome of ischemic stroke is an mRS of 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation